2018
DOI: 10.1098/rstb.2018.0018
|View full text |Cite
|
Sign up to set email alerts
|

Are fungal strains from salinized streams adapted to salt-rich conditions?

Abstract: One contribution of 23 to a theme issue 'Salt in freshwaters: causes, ecological consequences and future prospects'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Thus, the underlying mechanisms for reduced decomposition remain controversial. Whereas a recent study [68] showed that fungal decomposers obtained from both salinized and undisturbed sites largely maintained their function at experimental high salinity concentrations, a previous study [39] revealed lower leaf decomposition rates for microorganism communities from a salinized reach compared with those from an undisturbed site, which may hint towards a salinity-driven selection of less efficient bacterial decomposers. Despite the rather consistent reduction in decomposition with increased salinity, many other factors, such as nutrient availability, litter type and temperature, affect decomposition rates [46,65].…”
Section: (B) Leaf Litter Decompositionmentioning
confidence: 75%
“…Thus, the underlying mechanisms for reduced decomposition remain controversial. Whereas a recent study [68] showed that fungal decomposers obtained from both salinized and undisturbed sites largely maintained their function at experimental high salinity concentrations, a previous study [39] revealed lower leaf decomposition rates for microorganism communities from a salinized reach compared with those from an undisturbed site, which may hint towards a salinity-driven selection of less efficient bacterial decomposers. Despite the rather consistent reduction in decomposition with increased salinity, many other factors, such as nutrient availability, litter type and temperature, affect decomposition rates [46,65].…”
Section: (B) Leaf Litter Decompositionmentioning
confidence: 75%
“…This ion stress could result in mortality from the increased energy expenditure and investment in morphological structures that are required to maintain homeostasis [23,[36][37][38][39]. Whereas aquatic and terrestrial fungal activity may not show measureable changes until intermediate or highly elevated salinities occur and thus buffer ecosystem effects [40][41][42]. However, the mechanisms responsible for the biological response remain uncertain [35,43,44] and ion concentrations below those that result in species loss (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, we cannot rule out the possibility of a strategy shift of fungi in this treatment. It would be possible that unfavorable conditions imposed by the finest sediment lead fungi to invest more energy in reproduction (spore production) crucial for colonization of other substrata in more favorable conditions, as has been suggested in response to other alterations, such as temperature (Chauvet & Suberkropp, ) and salinization (Gonçalves, Carvalho, Bärlocher, & Canhoto, ). Although the effects on sporulation rate were grain‐size‐dependent, the presence of sediment per se and independently of the granulometry resulted in an alteration of the fungal assemblages’ structure.…”
Section: Discussionmentioning
confidence: 98%